2013
DOI: 10.5152/akd.2013.181
|View full text |Cite
|
Sign up to set email alerts
|

Human left atrial appendage anatomy and overview to its clinical significance

Abstract: Objective: The left atrial appendage (LAA) is an important anatomic region since it is a source of thromboembolism in patients with atrial fibrillation. Although this anatomic and clinical relation it has received little attention until recent years. Methods: This descriptive laboratory study was performed in 56 hearts of adult formalin fixed cadavers. The morphological characteristics of LAA were recorded. The distances between the orifices of left superior pulmonary veins (LSPV), circumflex artery, left ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
15
0
4
Order By: Relevance
“…In autopsy specimens and imaging studies, the LAA ostium is usually elliptical or round and in elliptical-shaped variant and its long axis is obliquely orientated relative to the mitral annulus [52, 53]. The LAA interior surface is lined by complicated network of fine pectinate muscles.…”
Section: Left Atrial Appendagementioning
confidence: 99%
“…In autopsy specimens and imaging studies, the LAA ostium is usually elliptical or round and in elliptical-shaped variant and its long axis is obliquely orientated relative to the mitral annulus [52, 53]. The LAA interior surface is lined by complicated network of fine pectinate muscles.…”
Section: Left Atrial Appendagementioning
confidence: 99%
“…One of the potential reasons for the learning curve is that the LAA is a three-dimensional entity. There are variations in shape, lobe number, and orifice diameter [5]. Some shapes, such as "cauliflower" shape, may be more associated in strokes in patients with low CHADS 2 scores [6].…”
Section: Discussionmentioning
confidence: 99%
“…In this study7 a lobe was anatomically defined as: (1) a visible ‘outpouching’ from the main tubular LAA, often demarcated externally by a ‘crease’; (2) able to accept a 2 mm probe internally; (3) possibly associated with a change in the main tubular LAA direction; and (4) lying in a different plane from the main tubular LAA. In a recent autopsy study, two and three lobes were observed in 64.3% and 35.7% of specimens, respectively 8. Accurate sizing of the LAA and knowledge of its gross morphological features are crucial to reduce the frequency of complications associated with percutaneous LAA occlusion (box 1).…”
Section: Morphological Variants Of the Laamentioning
confidence: 99%
“…In autopsy specimens and imaging studies, the LAA ostium is usually elliptical or round and in elliptical-shaped variant, its long axis is obliquely orientated relative to the mitral annulus 8 11. The mean longest diameter of the LAA orifice is 16–17 mm and the mean shortest diameter is around 10–11 mm 8 11.…”
Section: Ostium Of the Laamentioning
confidence: 99%
See 1 more Smart Citation